Representasi Afrika dalam Lagu “Do They Know It’s Christmas?” oleh Band Aid” (1984) - Yuana, Made Tarita Kezaravijaya (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2024)
The relationship between popular culture and world politics is an exciting study in the study of International Relations. One of the products of popular culture is a song. This article will examine one of the charity songs for famine in Ethiopia entitled "Do They Know It's Christmas?" belongs to Band Aid whose lyrics have many misinterpretations from the depiction of the country of Ethiopia, especially the African continent. The data that supports this paper were obtained online from accurate institutions and used content analysis methods. This paper uses the concept of the relationship between popular culture and world politics as multifaceted and independent. Popular culture has a complex impact on world politics. The result is that the representation of Africa in the song does not represent the actual state of the continent. Even though Band Aid, a non-state actor, is involved with humanitarian issues, they unite into an organization carrying out fundraising calls. The lyrics are baseless and inaccurate, it makes this Christmas carol contain a misunderstanding about Ethiopia. This song leaves Ethiopia with a negative stigma that developing countries are synonymous with poverty, hunger, and unmet needs that have implications for public relations problems and broader implications for tourism, investment, and other opportunities required for self-governance and autonomy. Keywords: Band Aid, Ethiopia, Lyrics, Stigma